Fund accounting for Malaysian federal government is it still relevant? - Kalsom Salleh; Rozainun Ab Aziz; Nurli Abu Bakar (Institut Perakaunan Negara, Jabatan Akauntan Negara Malaysia Universiti Teknologi MARA, 2013)
"The main objective of this paper is to provide literature evidence to support on the relevance of fund accounting in cash basis of financial statements of Federal Government in Malaysia and the accrual basis of financial statements in the developed countries." -- Abstract